2008
DOI: 10.1055/s-2008-1034311
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of New Cannabis Constituents from a High Potency Variety

Abstract: Phytochemical investigation of a high potency variety of Cannabis sativa L. resulted in the isolation of six new metabolites, (±)-6,7-trans-epoxycannabigerolic acid (2), (±)-6,7-cisepoxycannabigerolic acid (3), (±)-6,7-cis-epoxycannabigerol (4), (±)-6,7-trans-epoxycannabigerol (5), 5′-methyl-4-pentylbiphenyl-2,2′,6-triol (7), and 7-methoxycannabispirone (8), along with seven known compounds namely, cannabigerolic acid (1), 5′-methoxycannabigerolic acid (6), cannabispirone (9), β-cannabispiranol (10), dehydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 17 publications
1
79
0
Order By: Relevance
“…Isolated compounds were evaluated for antimicrobial ( Candida albicans ATCC 90028, Escherichia coli ATCC 35218, Pseudomonas aeruginosa ATCC 27853, Mycobacterium intracellulare ATCC 23068, Aspergillus fumigatus ATCC 90906, Methicillin Resistant S. aureus ATCC 43300), antileishmanial and antimalarial activity [ P. falciparum (D6 clone) and P. falciparum (W2 clone)] (Radwan et al, 2008a,b), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolated compounds were evaluated for antimicrobial ( Candida albicans ATCC 90028, Escherichia coli ATCC 35218, Pseudomonas aeruginosa ATCC 27853, Mycobacterium intracellulare ATCC 23068, Aspergillus fumigatus ATCC 90906, Methicillin Resistant S. aureus ATCC 43300), antileishmanial and antimalarial activity [ P. falciparum (D6 clone) and P. falciparum (W2 clone)] (Radwan et al, 2008a,b), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Modification of the structures are limited to changes in the side-chain and the terpenoid portion of the molecule (ElSohly and Slade, 2005). The total number of natural cannabinoids identified in C. sativa L. was 66 in 1995, 70 in 2005 and 105 in 2014 (Ahmed et al, 2008a,b; Appendino et al, 2008; Radwan et al, 2008a,b, 2009; ElSohly and Slade, 2005; ElSohly and Gul, 2014; Ross and ElSohly, 1995). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of new cannabis constituents were identified, increasing the total from 489 in 2005 (ElSohly and Slade, 2005) to 537 in 2009 (Ahmed et al, 2008a,b; Appendino et al, 2008; Radwan et al, 2009, 2008a,b), while the number of cannabinoids increased from 70 to 109. The cannabinoids are the most studied cannabis constituents, in particular Δ 9 -tetrahydrocannabinol (Δ 9 -THC), the main psychoactive component (Galal et al, 2009); however, research has shown that some of the other cannabinoids also exhibit pharmacological activities, e.g., the nonpsychotropic cannabinoid cannabidiol (CBD) displays antihyperalgesic, antipsychotic, anticonvulsant, neuroprotective and antiemetic properties (Galal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cannflavin A and B, two methylated isoprenoid flavones, represent the first aglycone flavonoids uniquely isolated from cannabis. The antileishmanial activity for cannflavin A and B was reported as strong (IC 50 10.3 μM) (Radwan et al, 2008a) and moderate (IC 50 13.6 μM) (Radwan et al, 2008b), respectively.…”
Section: Introductionmentioning
confidence: 99%